2016
DOI: 10.1080/20445911.2015.1134541
|View full text |Cite
|
Sign up to set email alerts
|

Children's creation of algorithms: simulations and gestures

Abstract: for advice.Experiments showed that ten-year old children are able to create algorithms, i.e., sequences of operations that solve problems, and that their gestures help them to do so. The theory of mental models, which is implemented in a computer program, postulates that the creation of algorithms depends on kinematic mental simulations. Gestures are outward signs of moves and they help the process. We tested ten-year children, because they can make mental simulations, and because they gesture more than adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
(63 reference statements)
2
13
0
Order By: Relevance
“…To the best of our knowledge, no previous study has obtained such a result. The results also corroborated our earlier finding that children could abduce algorithms for trains of six cars (Bucciarelli et al, 2016). In sum, the results corroborated the three predictions of the model theory.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…To the best of our knowledge, no previous study has obtained such a result. The results also corroborated our earlier finding that children could abduce algorithms for trains of six cars (Bucciarelli et al, 2016). In sum, the results corroborated the three predictions of the model theory.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, in a previous study of fifth-grade children, we examined two of the three tasks. We showed that children can solve problems of rearranging five cars, and that they can abduce informal algorithms for rearranging trains of six cars (Bucciarelli, Mackiewicz, Khemlani, & Johnson-Laird, 2016). We also showed that gestures helped them abduce algorithms when they were not allowed to move the cars.…”
mentioning
confidence: 83%
See 3 more Smart Citations